Genomic Landscape of Intramedullary Spinal Cord Tumors Suggests Distinct Genetic Origins Compared to Intracranial Histopathologic Counterparts. (1st September 2019) - Azad, Tej D; Zhang, Ming; Iyer, Rajiv; Wang, Qing; Garzon-Muvdi, Tomas; Wang, Joanna; Liu, Ann; Burger, Peter C; Eberhart, Charles G; Rodriguez, Fausto J; Sciubba, Daniel M; Wolinsky, Jean-Paul; et al.
Abstract: INTRODUCTION: Intramedullary spinal cord tumors (IMSCTs) are a rare, heterogeneous group of neoplasms with limited treatment options and high rates of morbidity and mortality. Next-generation sequencing has revealed opportunities for targeted therapies of the intracranial counterparts of IMSCT, but little is known about the molecular features of IMSCT. METHODS: To better understand the genetic basis of these tumors we performed whole exome sequencing on fifty-one IMSCT and matched germline DNA, including 29 ependymomas, 16 astrocytomas, 4 gangliogliomas, 1hemangioblastoma, and 1 oligodendroglioma. Whole-genome sequencing was further performed on 12 IMSCT to discover possible structural variants. RESULTS: Though recurrent somatic mutations in IMSCTs were rare, we identified NF2 mutations in 15.7% of tumors (ependymoma, N = 7; astrocytoma, N = 1), RP1 mutations in 5.9% of tumors (ependymoma, N = 3), and ESX1 mutations in 5.9% of tumors (ependymoma, N = 3). We further identified copy number amplifications in CTU1 in 25% of myxopapillary ependymomas. Given the paucity of somatic driver mutations, we further performed whole-genome sequencing of 12 tumors (ependymoma, N = 9; astrocytoma, N = 3). Overall, we observed that IMSCTs with intracranial histologic counterparts did not harbor the canonical mutations associated with their intracranial counterparts (eg glioblastoma). CONCLUSION: Our findings suggest that the origin of IMSCTs may be distinct from tumors arising within other compartments of the central nervous system and provides a framework to begin more biologically based therapeutic strategies.